Optimasi Konten Instagram dalam Strategi Promosi Bisnis Foto Pernikahan Sekawan Stories - Anis Yaasir Musthofa; Budi Istiyanto (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Photography has grown rapidly, especially in the wedding photography industry which now requires an effective business promotion strategy. This research aims to identify how business people utilize Instagram as a promotional medium and strengthen Instagram content in Sekawan Stories' wedding photography business promotion strategy. Using a descriptive qualitative method, this study collected data through interviews and virtual ethnographic observations to understand how Sekawan Stories utilizes Instagram as a promotional medium. The results show that Sekawan Stories effectively utilizes various Instagram features, such as Feed, Instastory, Highlight, Video Reels, and Instagram Ads to increase visibility and audience engagement. Their marketing strategies include endorsements with well-known vendors, use of the Answer Question feature, conducting giveaways, and offering discounts at certain moments. Instagram provides a great opportunity for wedding photography businesses to expand their market reach and increase promotional effectiveness. By optimizing their content and marketing strategies on Instagram, Sekawan Stories managed to attract the attention of new customers, increase interaction, and strengthen relationships with existing customers. Overall, Instagram proved to be a highly effective platform in digital marketing strategies in the wedding photography industry.